Switchable synthesis of Z-homoallylic boronates and E-allylic boronates by enantioselective copper-catalyzed 1,6-boration - Luo, Yunfei; Wales, Steven M.; Korkis, Stamatis E.; Roy, Iain D.; Lewis, William; Lam, Hon Wai (Wiley, 2018)
The enantioselective Cu-catalyzed 1,6-boration of (E,E) α,β,γ,δ-unsaturated ketones is described, which gives homoallylic boronates with high enantiomeric purity and unexpectedly high Zselectivity. By changing the solvent, the outcome can be altered to give E-allylic boronates.